Pengaruh variasi bevel pada proses pengelasan SMAW terhadap kekuatan tarik material - Yusuf Rizal Fauzi; Anhar Khalid; Akmal Barry (Universitas Muhammadiyah Metro, 2022)
The strength of welded joints is influenced by a wide variety of factors. One of them is due to structural changes as a result of the heating process. In order for the connection between the two metal parts to have good quality, it is necessary to have a proper welding and the connection and the shape of the weld bevel are in accordance with the use of the results of the weld. Parameters in Shielded Metal Arc Welding (SMAW) welding include current strength, voltage, electrical polarity, and the angle of the joint used. These parameters make the basis for the right selection in order to get a good quality or connection quality. The purpose of this study was to determine the effect of bevel variations on the tensile strength test of the SMAW welding process connection on medium carbon steel material. The welding process is carried out using RB 26 type electrodes using a current of 100 A at 1 G welding position, welding is carried out on the material using V, I and double V bevel with 1 specimen per bevel. Based on the research that has been done, it can be concluded that the type of joint bevel has an important influence on the results of the weld. From the variation of the bevel that has the highest tensile strength value, it is V bevel rather than double V bevel and 1 bevel. Due to the variation of V bevel has a small distortion angle compared to double V bevel and I bevel. Optimal electric welding results depend on the welding process technique.